Multimodal texts and socio-cultural differences: A multimodal study of two hospital homepages - Kong, Lingwei (Opción, 2019)
This study, adopting the socio-semiotic multimodal approach (Bezemer & Kress, 2016), examines the multimodal features of two hospital homepages which were collected from University College London Hospitals (UCLH) in London, the UK and Nanfang Hospital (NH) in Guangzhou, China. As a result, the image-text relations suggest that both the writing and images speak a lot in the two hospital homepages. In conclusion, it is important for professionals to be highly aware of professional practices and social-cultural contexts so that they can have competences in using multimodal resources and constructing institutional homepages.